Long-term uninterrupted enzyme replacement therapy prevents liver disease in murine model of severe homocystinuria - Park, Insun; Hůlková, Helena; Krijt, Jakub; Kožich, Viktor; Bublil, Erez M; Majtan, Tomas (Human mutation, 2020)
Classical homocystinuria (HCU) is an inborn error of metabolism caused by loss of cystathionine β-synthase (CBS) activity with the concomitant buildup of homocysteine. In knockout (KO) mice, a mouse model of HCU, complete lack of CBS is neonatally lethal. Administration of OT-58, an enzyme therapy for HCU, during the first 5 weeks of life rescued KO mice survival by preventing liver disease. Here, we studied the impact of a long-term uninterrupted OT-58 treatment or its absence beyond the neonatal period on liver pathology and metabolism. Plasma and liver metabolites of KO mice on OT-58 treatment were substantially improved or normalized compared with those receiving vehicle. Increased plasma activities of alanine aminotransferase and aspartate aminotransferase of vehicle-injected KO mice suggested the progression of liver damage with age and lack of treatment. At 3 months of age, liver histology showed no signs of hepatopathy in both vehicle- and OT-58-treated KO mice. However, moderate to severe liver disease, characterized by steatosis, hepatocellular necroses, disorganized endoplasmic reticulum, and swollen mitochondria, developed in 6-month-old vehicle-injected KO mice. KO mice on OT-58 treatment remained asymptomatic and were indistinguishable from age-matched healthy controls. Long-term uninterrupted OT-58 treatment was essential to prevent severe liver disease in the KO mouse model of HCU.
Keywords: játra; Homocystinuria; homocysteine; rare disease; homocystinurie; enzyme replacement therapy; Liver Diseases; Female; cystathionine β-synthase; liver disease; zvířata; enzymová substituční terapie; myši; Mice; myši knockoutované; histology; nemoci jater; ženské pohlaví; Liver; Male; Mice, Knockout; Animals; Enzyme Replacement Therapy; mužské pohlaví; Disease Models, Animal; modely nemocí na zvířatech